How not to be popular - Ziegler, Jennifer, 1967- (Delacorte Press, 2008)
Seventeen-year-old Sugar Magnolia Dempsey is tired of leaving friends behind every time her hippie parents decide to move, but her plan to be unpopular at her new Austin, Texas, school backfires when other students join her on the path to "supreme dorkdom."